IMPLEMENTING THE AMANAH CONCEPT THROUGH BEHAVIORAL ACCOUNTING TO ASSESS MANAGERIAL PERFORMANCE AT BAZNAS, SOUTHEAST SULAWESI - Alfian Toar; Selvi; Salehaman (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to examine the implementation of the concept of amanah (trustworthiness) through a behavioral accounting approach in assessing managerial performance at BAZNAS of Southeast Sulawesi Province. The study explores how the value of amanah influences managerial behavior, accountability, transparency, and organizational performance in zakat management. This research employs a qualitative method with a descriptive approach. Data were collected through participant observation, in-depth interviews with key informants, and documentation. The behavioral accounting approach was applied to understand managerial behavior and responsibilities in managing zakat funds and organizational activities. The results indicate that the integration of the concept of amanah and behavioral accounting contributes positively to managerial performance and the organizational work environment at BAZNAS of Southeast Sulawesi Province. The value of amanah has been internalized by employees and management in carrying out their duties in accordance with Law Number 23 of 2011 concerning Zakat Management. This value promotes responsible, transparent, and accountable behavior in the management of zakat funds. Furthermore, the implementation of amanah fosters stakeholder trust and strengthens organizational credibility, supporting more effective governance and reinforcing public confidence in zakat management institutions. The findings suggest that integrating Islamic ethical values, particularly amanah, into managerial practices and behavioral accounting frameworks can strengthen governance, accountability, and organizational effectiveness in zakat institutions. This study also provides practical insights for policymakers and zakat management organizations in developing value-based governance systems that enhance institutional performance and stakeholder trust. This study provides an alternative perspective by integrating Islamic ethical values with behavioral accounting in evaluating managerial performance. It highlights the importance of trustworthiness as a key factor in improving accountability, organizational effectiveness, and stakeholder confidence within zakat management institutions.